2019
DOI: 10.1016/j.ijdevneu.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of pioglitazone, a selective peroxisome proliferator‐activated receptor‐γ agonist in prenatal valproic acid‐induced behavioral and biochemical autistic like features in Wistar rats

Abstract: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder in children. It is diagnosis by two main behavioral phenotypes i.e. social‐communication impairments and repetitive behavior. ASD is complex disorder with unsolved etiology due to multiple genes involvement, epigenetic mechanism and environmental factors. Valproic acid (VPA), a teratogen is known to induce characteristic features related to ASD in rodents. Numerous studies suggest the potential therapeutic effects of peroxisome proliferator‐activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 82 publications
3
26
0
Order By: Relevance
“…It is well known that VPA induced ASD possibly through chromatin remodelling by inhibition of HDAC activity [11], inhibition of GABA transaminase [12] or via the b-catenin-Ras-ERK-p21 pathway [13]. Interestingly, metformin has been shown to modulate HDAC activity [39], attenuates ERK signalling by activating AMPK pathway [40] and rescues multiple pathological phenotypes of fragile X syndrome in Drosophila [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that VPA induced ASD possibly through chromatin remodelling by inhibition of HDAC activity [11], inhibition of GABA transaminase [12] or via the b-catenin-Ras-ERK-p21 pathway [13]. Interestingly, metformin has been shown to modulate HDAC activity [39], attenuates ERK signalling by activating AMPK pathway [40] and rescues multiple pathological phenotypes of fragile X syndrome in Drosophila [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidences have shown that mitochondrial dysfunction and oxidative stress play significant role in ASD. Interestingly, autistic brains showed significant decrease in antioxidant enzymes activities, mitochondrial electron transport chainKyoto, Kyoto, Japan and ATP levels as well as increased levels of reactive oxygen species (ROS) and carbonyl proteins in comparison with normal unaffected control [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical studies, administering pioglitazone decreases inflammation and oxidative stress, thus reverting the ASD-like behavior [114]. The ASD-like behavioral deficits can be induced in rats with a postnatal treatment with propionic acid, which increases inflammation and oxidative stress [51].…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…In the brain, ASD is characterized by depletion of brain GSH (Glutathione), oxidative stress, and inflammation paralleled by neuroanatomical defects. The observations in humans have also been confirmed in animal models of disease, such as valproic-treated rats or propionic-treated rats [135,136].…”
Section: Pparγ and Autismmentioning
confidence: 88%